Detection of additional primary malignancies: the role of CT and PET/CT combined with multiple percutaneous biopsy - Tibana,Tiago Kojun (2019)
Abstract Objective: To evaluate the imaging findings of 18F-fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG PET/CT) and computed tomography (CT) in patients with additional primary tumors, correlating the results with those of the method used in order to elucidate the diagnosis and of the pathology reports. Materials and Methods: We retrospectively analyzed the medical records, pathology reports and images of 11 patients who underwent CT, 18F-FDG PET/CT, or both. We included patients with at least two tumors, with confirmed distinct histopathological profiles, at different sites. Patients in whom there was no diagnostic confirmation were excluded, as were those in whom the additional lesion was suspected of being a metastasis of the first. Results: New primary malignancies were identified in 11 patients, one new tumor being found in 10 and two new tumors being found in 1. The confirmed sites of the additional malignancies were the lung, kidney, prostate, jejunum, and breast. Single or multiple percutaneous biopsies were performed in 10 patients, and 1 patient underwent a surgical procedure for diagnostic and therapeutic purposes. The tumors were metachronous in 6 cases and synchronous in 5. Conclusion: CT and 18F-FDG PET-CT combined with multiple percutaneous biopsy could facilitate the diagnosis of additional lesions, thus optimizing the treatment and follow-up of the affected patients.